Self-supporting carbon electrode based on wood-bamboo material and preparation method and application thereof
Through the synchronous graphitization process of foam nickel packaging catalysis and high-temperature molten salt electrolytic activation of cobalt nickel alloy particles, the problems of insufficient performance and complex production of self-supported carbon electrodes in the prior art are solved, and the degree of graphitization and high performance are achieved. Self-supported carbon electrode, suitable for supercapacitors.
Patent Information
- Application Number
- CN202411422265.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-12
AI Technical Summary
In the prior art, when preparing self-supported carbon electrodes, it is difficult to achieve high degree of graphitization and high performance, and requires the use of highly corrosive chemical reagents, which is complex in operation and difficult to achieve large-scale production.
Through the synchronous graphitization process of foam nickel encapsulation catalysis and high-temperature molten salt electrolytic activation of synchronous graphitization, self-supported carbon electrodes based on wood and bamboo materials are prepared, avoiding the use of highly corrosive chemical reagents, and the process is simple and suitable for large-scale production.
A self-supported carbon electrode with high graphitization and high specific surface area has excellent electrochemical properties, no additional current collectors, binders and conductive agents are required, suitable for supercapacitors, simplifying the electrode structure and improving performance.
Smart Images

Figure CN119400608A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrodes, and in particular to a self-supporting carbon electrode based on wood and bamboo materials, and a preparation method and application thereof. Background Art
[0002] Supercapacitors, with their high power density, long cycle life and fast charge and discharge capabilities, have shown great application potential in electric vehicles, smart grids, portable electronic devices and other fields. Among them, the performance of the electrode directly determines the overall performance of the supercapacitor. Therefore, the development of high-performance, low-cost and environmentally friendly electrode materials has become a research focus in this field.
[0003] Currently, carbon materials such as activated carbon, graphene and carbon nanotubes are widely used in the preparation of supercapacitor electrodes. However, these materials are usually used in powder form, and inactive ingredients such as binders, conductive agents and additional current collectors need to be introduced during the electrode manufacturing process, thereby reducing the specific capacity performance of the complete electrode.
[0004] In contrast, self-supporting carbon electrodes integrate current collectors and active materials, do not require additional conductive agents and binders, and can maximize the utilization of all components of the electrode for energy storage. They are considered to be the representatives of the next generation of high-performance supercapacitor electrodes.
[0005] Existing methods for making self-supporting carbon electrodes include in-situ activation of carbon cloth and graphitized fiber paper, self-assembly of graphene sheets, assembly of carbon nanotube arrays into films, and spinning of carbon nanotubes into fibers. Although these methods can produce electrodes with high specific surface area and good conductivity, they often involve complex, highly corrosive, and high-temperature chemical reactions, or are limited by material sources and costs, making it difficult to achieve large-scale production.
[0006] In recent years, biomass materials have become a new direction in electrode material research due to their renewability, low cost and abundant resources. Wood chips and bamboo chips, as common biomass resources, have great potential as electrode material precursors due to their natural porous structure and rich carbon content. However, the preparation of self-supporting carbon electrodes based on wood and bamboo materials still faces challenges.
[0007] Although the traditional carbonization-gas activation method can increase the specific surface area of the electrode, it is difficult for the gas activator to fully contact the precursor in advance, and long-term high-temperature activation is required, resulting in high energy consumption, low efficiency, and possible damage to the self-supporting structure.
[0008] The carbonization-chemical activation method can prepare wood-bamboo-based porous carbon electrodes with high specific surface area in a shorter time and at a lower temperature, but highly corrosive chemical reagents will severely etch the wood-bamboo carbon skeleton and destroy its structural integrity.
[0009] In addition, the low degree of graphitization of wood and bamboo materials after carbonization and activation limits their rate performance and cycle stability.
[0010] Therefore, developing a new method that does not require the use of highly corrosive chemical reagents, is simple to operate, and can prepare a high-graphitization, high-performance self-supporting carbon electrode has become a key issue that needs to be urgently addressed in the current supercapacitor field. Summary of the invention
[0011] In view of the above technical problems and the shortcomings in the art, the present invention provides a self-supporting carbon electrode based on wood and bamboo materials and a preparation method and application thereof. The preparation method provided by the present invention has a simple process, renewable raw materials and low cost, and is easy to achieve large-scale production.
[0012] The present invention proposes an innovative method for preparing a self-supporting carbon electrode based on wood and bamboo materials. Through the synchronous graphitization process of nickel foam encapsulation catalysis loaded with cobalt-nickel alloy particles and high-temperature molten salt electrolysis activation, it effectively overcomes the limitations of the existing technology and provides a new way for the large-scale production of high-performance supercapacitor electrodes.
[0013] [1] A method for preparing a self-supporting carbon electrode based on wood and bamboo materials, comprising the steps of:
[0014] (1) fully carbonizing a wood-bamboo sheet having transparent pores in an inert atmosphere to obtain a wood-bamboo carbon sheet;
[0015] (2) The nickel foam is immersed in a solution containing cobalt acetate and nickel acetate, then taken out and dried, wrapped with wood and bamboo carbon sheets, and subjected to a load of 5 to 15 kN / m 2 (e.g. 10kN / m 2 The nickel foam is squeezed under the pressure of the carbon fiber, so that it is in full contact with all surfaces of the wood and bamboo carbon sheet;
[0016] (3) The wood and bamboo carbon sheet wrapped with nickel foam obtained in step (2) is fixed on a first conductive support as a working electrode, and placed together with a counter electrode and a reference electrode in a molten salt electrolyte under an inert atmosphere for electrolysis, a voltage of -2.1 to -2.3 V (e.g., -2.15 V, -2.2 V, etc.) is applied to the working electrode, and electrolysis is performed for 8 to 12 hours (e.g., 10 hours, etc.) to achieve pore formation and graphitization. After the electrolysis is completed, the wood and bamboo carbon sheet sample is taken out from the nickel foam, washed, and dried to obtain a self-supporting carbon electrode.
[0017] In step (1), the method for preparing the wood-bamboo sheet having transparent pores may include:
[0018] The peeled bamboo is cut into bamboo chips (for example, along the vertical growth direction), polished and then soaked in a mixed aqueous solution of formic acid-hydrochloric acid-ethanol to thoroughly clean the extract and inorganic salt in the bamboo pipes, then taken out, washed and dried to obtain the bamboo chips with transparent pores.
[0019] In the method for preparing the wood-bamboo slices with transparent pores, the size of the cut wood-bamboo slices can be: 2 cm in width, 3 cm in length, and 0.3 cm in thickness.
[0020] In the method for preparing the wood and bamboo pieces with transparent pores, 400-mesh sandpaper can be used at 30 kN / m 2 The grinding is performed under a pressure of .
[0021] In the method for preparing the wood-bamboo chip with transparent pores, the mixed aqueous solution of formic acid-hydrochloric acid-ethanol can be obtained by mixing a formic acid aqueous solution, a hydrochloric acid aqueous solution and ethanol.
[0022] In the preparation method of the wood and bamboo chips with transparent pores, in the mixed aqueous solution of formic acid-hydrochloric acid-ethanol, the total concentration of formic acid, hydrochloric acid and ethanol can be 0.8-1.5 mol / L, such as 1 mol / L, the molar ratio of formic acid to hydrochloric acid can be 0.05-0.2:1, and the molar ratio of ethanol to hydrochloric acid can be 0.08-0.12:1, such as 0.1:1.
[0023] In the method for preparing the wood-bamboo slices with transparent pores, deionized water and ethanol may be used for washing until the pH value of the wood-bamboo slices reaches 7.
[0024] In the method for preparing the wood-bamboo slice with transparent pores, the drying may be performed by vacuum drying, and the drying temperature may be 50°C.
[0025] In step (1), the wood and bamboo chips may include one or more of pine chips, bamboo chips, fir chips, etc.
[0026] In the present invention, the inert atmosphere refers to a gas atmosphere that does not participate in the reaction.
[0027] In step (1), the inert atmosphere may be a nitrogen atmosphere.
[0028] In step (1), the carbonization temperature may be 800-1000° C. (eg, 900° C.), the heating rate may be 3-5° C. / min, and the carbonization time may be 1-2 hours.
[0029] In step (1), after carbonization, the temperature can be lowered to 500° C. at a rate of 3 to 5° C. / min, and then naturally lowered to room temperature.
[0030] In step (1), the carbonized product is polished, cleaned and dried to obtain a wood-bamboo carbon sheet.
[0031] In step (1), the carbonized product can be polished using 220-mesh sandpaper.
[0032] In step (1), the carbonized product can be polished to obtain a cuboid with a width of 1 cm, a length of 2 cm, and a thickness of 0.1 cm.
[0033] In step (1), the carbonized product can be polished and washed with deionized water and ethanol.
[0034] In step (1), the carbonized product is polished and leveled, and after washing, the drying can be performed by vacuum drying, and the drying temperature can be 60°C.
[0035] In step (2), the thickness of the nickel foam may be 1 to 2 mm, the porosity may be 95% to 98%, and the pore size may be 0.2 to 0.5 mm, such as 0.3 mm.
[0036] In step (2), in the solution containing cobalt acetate and nickel acetate, the total concentration of cobalt acetate and nickel acetate can be 5-10 mmol / L (e.g., 7 mmol / L, etc.), and the molar ratio of cobalt acetate to nickel acetate can be 1-3:1, e.g., 2:1, etc.
[0037] In step (2), the solvent in the solution containing cobalt acetate and nickel acetate may be ethanol.
[0038] In step (2), the nickel foam is immersed in the solution containing cobalt acetate and nickel acetate for 5 to 15 minutes, for example, 10 minutes.
[0039] In step (3), 304 stainless steel wire can be used to fix the wood-bamboo carbon sheet wrapped with nickel foam on the first conductive support as a working electrode.
[0040] In step (3), the first conductive support may be a stainless steel conductive support.
[0041] In step (3), the nickel-chromium alloy rod fixed on the second conductive bracket can be used as a counter electrode and a reference electrode.
[0042] In step (3), the second conductive support may be a stainless steel conductive support.
[0043] In step (3), the inert atmosphere may be an argon atmosphere.
[0044] In step (3), the temperature of the molten salt electrolyte may be 850-950°C, for example, 900°C.
[0045] In step (3), the molten salt electrolyte may be a mixed molten salt of sodium carbonate and potassium carbonate.
[0046] In step (3), in the molten salt electrolyte, based on the total molar number of sodium carbonate and potassium carbonate as 100%, the molar proportion of sodium carbonate can be 55% to 65%, for example, 59%.
[0047] In step (3), the washing can be performed using hydrochloric acid and deionized water in sequence, wherein the hydrochloric acid is used to wash away the residual salt, and the deionized water is used to wash the wood and bamboo carbon sheet sample until the pH reaches neutral.
[0048] In step (3), the drying may be performed by vacuum drying, and the drying temperature may be 60°C.
[0049] [2] A self-supporting carbon electrode prepared according to the preparation method described in [1].
[0050] The self-supporting carbon electrode of the present invention has self-supporting ability, high specific surface area (can exceed 1000m 2 / g) and excellent degree of graphitization.
[0051] [3] Use of the self-supporting carbon electrode according to [2] in the preparation of a supercapacitor electrode. The self-supporting carbon electrode of the present invention can be directly used as a supercapacitor electrode without the need for an additional current collector, a binder and a conductive agent. Furthermore, the supercapacitor may be a zinc ion supercapacitor or a lithium ion supercapacitor. The self-supporting carbon electrode exhibits excellent electrochemical properties in zinc ion and lithium ion supercapacitors and is a potential candidate for electrode materials.
[0052] The self-supporting carbon electrode of the present invention uses wood and bamboo sheets as raw materials, is encapsulated and catalyzed by nickel foam loaded with cobalt-nickel alloy particles, and is subjected to high-temperature molten salt electrolysis to achieve key conversion. The carbon sheet material produced by this process not only has self-supporting ability, but also has a high specific surface area and excellent degree of graphitization. More importantly, this carbon sheet can integrate the functions of fluid and active material and be directly used as an electrode of a supercapacitor, thereby simplifying the electrode structure and improving performance.
[0053] The core steps of the preparation method of the present invention are as follows: first, the wood and bamboo materials are precisely cut to obtain sheets of the required size; then, the sheets are soaked and cleaned. Next, a carbonization treatment is performed in an inert atmosphere environment to obtain a wood and bamboo carbon sheet material. Thereafter, the wood and bamboo carbon sheet is wrapped and packaged under a constant pressure using nickel foam whose surface is pre-adsorbed with cobalt acetate and nickel acetate. After the packaging is completed, the entire package is used as a working electrode and placed in a high-temperature molten salt environment under an inert atmosphere for constant voltage electrolysis, and finally a self-supporting carbon electrode based on wood and bamboo materials is obtained.
[0054] The preparation method of the present invention has the significant advantage that there is no need to use highly corrosive alkali to make holes throughout the process, the operation process is simple, and the raw materials selected are renewable, low-cost and easy to obtain, so it has great potential for large-scale production. By using a nickel foam with cobalt acetate and nickel acetate adsorbed on the surface to wrap and encapsulate, the cobalt-nickel alloy particles formed by the pyrolysis of cobalt acetate and nickel acetate at high temperature can be effectively loaded on the nickel foam, and then catalyze the graphitization process on the surface of the wood and bamboo carbon sheet. In addition, by applying appropriate pressure to wrap and encapsulate, not only the close contact between the nickel foam and the surface of the wood and bamboo carbon sheet is ensured, it is conducive to the conduction of electron transfer and electrolytic reaction, and the catalyst is promoted to fully contact with the carbon substrate, and the catalytic effect is improved, while avoiding the destruction of the self-supporting structure of the carbon sheet by excessive pressure.
[0055] The present invention also cleverly utilizes high-temperature molten salt for electrolysis. This step not only realizes pore formation through direct chemical reaction between molten salt and carbon substrate, increases specific surface area and pore volume, but also creates a favorable environment for deoxidation of carbon materials and rearrangement of carbon atoms for graphitization, thereby significantly improving the overall conductivity of the material. The self-supporting carbon electrode prepared by the method of the present invention can be directly used as an electrode without the need for additional current collectors, binders and conductive agents. At the same time, due to its high specific surface area and high degree of graphitization, it exhibits excellent performance in supercapacitor applications.
[0056] The preparation method of the present invention has the following characteristics:
[0057] a) After drying, nickel foam, on which cobalt acetate and nickel acetate have been adsorbed, is used to encapsulate the wood and bamboo carbon sheet. The cleverness of this approach is that cobalt acetate and nickel acetate will form cobalt-nickel alloy particles after pyrolysis and be loaded on the nickel foam. This change is extremely beneficial for catalyzing the graphitization process on the surface of the wood and bamboo carbon sheet. Without the wrapping of nickel foam, the surface graphitization of the wood and bamboo carbon sheet will show significant unevenness, which will lead to a significant decrease in its electrochemical performance. In addition, if the surface of the nickel foam fails to adsorb cobalt acetate and nickel acetate, the degree and depth of graphitization of the wood and bamboo carbon sheet will be limited, and it will not be able to fully demonstrate its due electrochemical performance.
[0058] b) The pressure of extruding nickel foam is strictly controlled to ensure that it is between 5 and 15 kN / m 2 This control measure has a dual meaning: on the one hand, it can ensure close contact between the nickel foam and the surface of the wood and bamboo carbon sheet, which is conducive to the transfer of electrons and the electrolysis reaction; at the same time, it can also ensure full contact between the catalyst and the carbon substrate, so as to exert the best catalytic effect. On the other hand, by avoiding excessive pressure, we can effectively protect the self-supporting ability of the carbon sheet and prevent it from being damaged by excessive pressure.
[0059] c) During the electrolysis process, we also precisely controlled the voltage applied to the working electrode and the electrolysis time. Specifically, we selected a voltage range of -2.1V to -2.3V and set the electrolysis time to 8 to 12 hours. This choice is based on the following considerations: if the absolute voltage is too low or the electrolysis time is too short, the carbon sheet will not be able to complete sufficient graphitization and sufficient pore formation; if the absolute voltage is too high or the electrolysis time is too long, the carbon sheet will decompose due to excessive graphitization and excessive pore formation, and then lose its self-supporting ability. Therefore, through strict voltage and time control, we can ensure the preparation of wood and bamboo carbon sheets with excellent performance.
[0060] The core technical highlights of the present invention include the following points:
[0061] 1) The wood and bamboo carbon sheets are carefully wrapped and encapsulated with nickel foam whose surface is pre-adsorbed with cobalt acetate and nickel acetate. In this process, the cobalt-nickel alloy particles formed by the pyrolysis of cobalt acetate and nickel acetate will be firmly loaded on the nickel foam, which greatly promotes the graphitization process of the wood and bamboo carbon sheet surface.
[0062] 2) During the packaging process, we applied a precisely controlled pressure within a range that ensured close contact between the nickel foam and the surface of the wood and bamboo carbon sheet, facilitating efficient electron transfer and smooth electrolysis, while also ensuring full contact between the catalyst and the carbon substrate, thereby achieving the best catalytic effect. In addition, this pressure control also cleverly avoided damage to the self-supporting ability of the carbon sheet due to excessive pressure.
[0063] 3) The present invention also uses high-temperature molten salt electrolysis technology. This step not only utilizes the direct chemical reaction between the high-temperature molten salt and the carbon substrate, effectively increasing the specific surface area and pore volume of the material, but also creates a favorable environment for the deoxidation of the carbon material and the rearrangement and graphitization of carbon atoms, thereby significantly improving the overall conductivity of the material.
[0064] Compared with the prior art, the present invention has the following beneficial effects:
[0065] 1. The preparation process of the present invention completely avoids the use of highly corrosive alkali for pore formation, which not only simplifies the operation steps, but also reduces the requirements for the operating environment. At the same time, the selected raw materials are renewable, low-cost and easy to obtain. It is particularly worth mentioning that the molten salt used in the electrolysis process can be recycled, which further reduces the production cost and provides strong support for large-scale production.
[0066] 2. The present invention ingeniously uses nickel foam with cobalt acetate and nickel acetate pre-adsorbed on the surface to encapsulate the wood and bamboo carbon sheet. This innovative technology enables the cobalt-nickel alloy particles formed after pyrolysis of cobalt acetate and nickel acetate to be firmly loaded on the nickel foam, thereby effectively catalyzing the surface graphitization of the wood and bamboo carbon sheet under molten salt electrolysis conditions. This discovery provides a new idea for research in related fields and has not yet been reported.
[0067] 3. The present invention successfully realized the efficient preparation of self-supporting carbon electrodes using wood and bamboo materials by molten salt electrolysis for the first time. This breakthrough has opened up a new way for the efficient utilization of wood and bamboo materials.
[0068] 4. The self-supporting carbon electrode prepared by the method of the present invention can be directly used as an electrode without additional current collectors, binders and conductive agents, which greatly simplifies the preparation process of the electrode. At the same time, the electrode has a high specific surface area and a high degree of graphitization, which makes it exhibit excellent application performance in supercapacitors, providing new possibilities for improving the performance of supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] Figure 1 This is an actual optical photograph of the self-supporting carbon electrode prepared in Example 1.
[0070] Figure 2 , Figure 3 Scanning electron microscope photos of the self-supporting carbon electrode prepared in Example 1 at different angles.
[0071] Figure 4 This is a comparison chart of the X-ray diffraction (XRD) of the self-supporting carbon electrode (after electrolysis) prepared in Example 1 and the charcoal precursor (before electrolysis).
[0072] Figure 5 Comparison of nitrogen adsorption-desorption curves, specific surface areas and pore volumes of the self-supporting carbon electrode (after electrolysis) and the charcoal precursor (before electrolysis) prepared in Example 1. DETAILED DESCRIPTION
[0073] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0074] Example 1
[0075] (I) Preparation of self-supporting carbon electrodes
[0076] Step 1: Preparation of pine wood chips
[0077] The peeled pine wood was precisely cut into pine wood pieces with a size of 2 cm × 3 cm × 0.3 cm along the vertical growth direction using a precision panel saw.
[0078] At 30kN / m 2 Under pressure, use 400-grit sandpaper to carefully sand both surfaces of the pine wood chips to remove surface powder and ensure that the surface of the pine wood chips is flat and clean.
[0079] Step 2: Processing and cleaning of pine wood chips
[0080] The flat pine wood chips were soaked in a mixed aqueous solution of formic acid-hydrochloric acid-ethanol (molar ratio of 0.1:1:0.1) with a total concentration of 1 mol / L at room temperature for 10 hours to thoroughly clean the extracts and inorganic salts in the pine wood pipes.
[0081] Subsequently, the pine wood chips were soaked in deionized water at room temperature for 2 h and washed repeatedly until the pH value was close to 7.0.
[0082] Rinse once more with 95% ethanol to ensure thorough cleaning.
[0083] The cleaned pine wood chips were placed in a vacuum oven at 50° C. and dried for 24 hours to obtain pine wood chips with transparent pores.
[0084] Step 3: Carbonization of pine wood chips
[0085] The pine wood chips with transparent pores were placed in a tubular furnace, and slowly heated to 1000°C at a heating rate of 3°C / min under nitrogen protection, and kept warm for 1 hour to fully carbonize the pine wood chips.
[0086] After carbonization, the temperature was lowered to 500 °C at a rate of 5 °C / min and then naturally cooled to room temperature.
[0087] Take out the pine wood carbon sheet, use 220-grit sandpaper to smooth the collapsed or raised parts of the surface, and finally polish it into a rectangular block with a size of 1 cm×2 cm×0.1 cm.
[0088] After being rinsed alternately with deionized water and 95% ethanol, the carbon sheets were dried in a vacuum oven at 60°C for 12 hours to obtain pine carbon sheets with uniform specifications, certain conductivity, smooth surface and transparent pores.
[0089] Step 4: Treatment of nickel foam and molten salt electrolysis of pine wood carbon sheets
[0090] Clean nickel foam (1 mm thick, 99.9% purity, 95% porosity, 0.2 mm pore size) was taken and immersed in a mixed solution of cobalt acetate and nickel acetate (molar ratio of 1.0) in ethanol with a total concentration of 5 mmol / L for 10 minutes.
[0091] Take out the nickel foam, spread it flat in a glass container, and let it dry naturally at room temperature.
[0092] A rectangular pine carbon sheet with transparent pores was wrapped with dried nickel foam and subjected to a load of 10 kN / m 2 The nickel foam is squeezed under pressure to ensure that it is in full contact with all surfaces of the pine wood carbon sheet.
[0093] The nickel foam-wrapped pine wood carbon sheet was fixed on a stainless steel conductive support using 304 stainless steel wire as the working electrode.
[0094] This working electrode, together with a nickel-chromium alloy rod fixed on a stainless steel conductive support (as a counter electrode and a reference electrode), was placed in an 850°C molten salt electrolyte (Na2CO3 / K2CO3 molar ratio of 59:41) under an argon atmosphere for electrolysis.
[0095] A voltage of -2.15 V was applied to the working electrode, and electrolysis was performed for 10 hours.
[0096] After the electrolysis was completed, the sample was cooled to room temperature, taken out from the nickel foam, and immersed in 1 M hydrochloric acid to remove the residual carbonate.
[0097] The sample was rinsed with deionized water until the pH reached neutral and dried under vacuum at 60 °C for 12 h to obtain a self-supporting carbon electrode.
[0098] Figure 1 Actual optical images of the self-supporting carbon electrode prepared in this example are presented, clearly demonstrating its excellent self-supporting properties. Figure 2 and Figure 3 The scanning electron microscope images of the self-supporting carbon electrode were displayed from different observation angles, revealing the rich channel structure inside the electrode, a feature that makes it very suitable for application in the field of supercapacitors. Figure 4 It was further demonstrated that after the molten salt electrolysis reaction, the degree of graphitization of the self-supporting electrode was significantly improved compared to before electrolysis. Figure 5 It shows that after the molten salt electrolysis reaction, the specific surface area and pore volume of the self-supporting electrode have been greatly improved compared with before electrolysis.
[0099] (II) Application performance test of self-supporting carbon electrodes
[0100] This time, its application in zinc ion supercapacitors was tested. The self-supporting carbon electrode was used as the working electrode, and the zinc foil electrode was used as the counter electrode and reference electrode. Through the double electrode system, the prepared electrode was subjected to constant current charge and discharge tests (charge and discharge voltage range 0.2-1.8V) in 2M ZnSO4 electrolyte at room temperature using a battery charge and discharge equipment (CT2001A, Wuhan Blue Electric Electronics Co., Ltd.).
[0101] According to the formula C = I × △t / M, the specific capacity C of the prepared sample at different charge and discharge current densities can be calculated based on the charge and discharge curve. Where △t (h) represents the discharge time, I (mA) represents the discharge current, and M (g) represents the mass of the entire self-supporting electrode material.
[0102] The results show that at 2.0 mA / cm 2 Under the current density, the mass specific capacity of the prepared self-supporting carbon electrode can reach 67 mAh / g, indicating that the self-supporting carbon electrode prepared by the method of the present invention has excellent electrochemical properties and is a potential candidate for zinc ion supercapacitor electrode.
[0103] Example 2
[0104] (I) Preparation of self-supporting carbon electrodes
[0105] Step 1: Preparation of bamboo slices
[0106] The peeled bamboo stalks were precisely cut into bamboo pieces with a size of 2 cm×3 cm×0.3 cm using a precision panel saw.
[0107] At 30kN / m 2 Under pressure, use 400-grit sandpaper to carefully polish the two surfaces of the bamboo slices to remove surface powder and ensure that the surface of the bamboo slices is flat and clean.
[0108] Step 2: Processing and cleaning of bamboo pieces
[0109] The flat bamboo pieces were immersed in a mixed aqueous solution of formic acid-hydrochloric acid-ethanol (molar ratio of 0.2:1:0.1) with a total concentration of 1 mol / L at room temperature for 10 hours to thoroughly clean the extracts and inorganic salts in the bamboo pipes.
[0110] Subsequently, the bamboo pieces were soaked in deionized water at room temperature for 2 h and washed repeatedly until the pH value was close to 7.0.
[0111] Rinse once more with 95% ethanol to ensure thorough cleaning.
[0112] The cleaned bamboo slices were placed in a vacuum oven at 50° C. and dried for 24 hours to obtain bamboo slices with transparent pores.
[0113] Step 3: Carbonization of bamboo pieces
[0114] The bamboo slices with transparent pores were placed in a tubular furnace, and slowly heated to 900°C at a heating rate of 5°C / min under nitrogen protection, and kept warm for 1 hour to fully carbonize the bamboo slices.
[0115] After carbonization, the temperature was lowered to 500 °C at a rate of 5 °C / min and then naturally cooled to room temperature.
[0116] Take out the bamboo carbon sheet, use 220-grit sandpaper to smooth the collapsed or raised parts of the surface, and finally polish it into a rectangular block with a size of 1 cm×2 cm×0.1 cm.
[0117] After being rinsed alternately with deionized water and 95% ethanol, the carbon sheets were dried in a vacuum oven at 60°C for 12 hours to obtain bamboo carbon sheets with uniform specifications, certain conductivity, smooth surface and transparent pores.
[0118] Step 4: Treatment of nickel foam and molten salt electrolysis of bamboo carbon sheets
[0119] Clean nickel foam (2 mm thick, purity 99.9%, porosity 98%, pore size 0.5 mm) was taken and immersed in a mixed solution of cobalt acetate and nickel acetate (molar ratio 2.0) in ethanol with a total concentration of 7 mmol / L for 15 minutes.
[0120] Take out the nickel foam, spread it flat in a glass container, and let it dry naturally at room temperature.
[0121] The dried nickel foam was used to wrap the rectangular bamboo carbon sheet with transparent pores and the carbon sheet was subjected to a load of 5 kN / m 2 The nickel foam is squeezed under a certain pressure to ensure that it is in full contact with all surfaces of the bamboo carbon sheet.
[0122] The nickel foam-wrapped bamboo carbon sheet was fixed on a stainless steel conductive support using 304 stainless steel wire as the working electrode.
[0123] This working electrode, together with a nickel-chromium alloy rod fixed on a stainless steel conductive support (as a counter electrode and a reference electrode), was placed in a 900°C molten salt electrolyte (Na2CO3 / K2CO3 molar ratio of 59:41) under an argon atmosphere for electrolysis.
[0124] A voltage of -2.2 V was applied to the working electrode, and electrolysis was performed for 8 hours.
[0125] After the electrolysis was completed, the sample was cooled to room temperature, taken out from the nickel foam, and immersed in 1 M hydrochloric acid to remove the residual carbonate.
[0126] The sample was rinsed with deionized water until the pH reached neutral and dried under vacuum at 60 °C for 12 h to obtain the self-supporting carbon material.
[0127] (II) Application performance test of self-supporting carbon electrodes
[0128] This time, its application in lithium-ion supercapacitors was tested. The self-supporting carbon electrode was used as the working electrode, and the commercial graphite electrode was used as the counter electrode and reference electrode. Through the two-electrode system, the prepared electrode was subjected to constant current charge and discharge tests (charge and discharge voltage range 1.0-4.0V) in 1M LiPF6 electrolyte at room temperature using a battery charge and discharge equipment (CT2001A, Wuhan Blue Electric Electronics Co., Ltd.).
[0129] According to the formula C = I × △t / M, the specific capacity C of the prepared sample at different charge and discharge current densities can be calculated based on the charge and discharge curve. Where △t (h) represents the discharge time, I (mA) represents the discharge current, and M (g) represents the mass of the entire self-supporting electrode material.
[0130] The results show that at a current density of 100 mA / g, the mass specific capacity of the prepared self-supporting carbon electrode can reach 35 mAh / g, indicating that the self-supporting carbon electrode prepared by the method of the present invention has excellent electrochemical properties and is a potential candidate for lithium ion supercapacitor electrode.
[0131] Example 3
[0132] (I) Preparation of self-supporting carbon electrodes
[0133] Step 1: Preparation of fir chips
[0134] The peeled fir was precisely cut into fir pieces with a size of 2 cm×3 cm×0.3 cm along the vertical growth direction using a precision panel saw.
[0135] At 30kN / m 2 Under pressure, use 400-grit sandpaper to carefully sand both surfaces of the fir chips to remove surface powder and ensure that the surface of the fir chips is flat and clean.
[0136] Step 2: Processing and cleaning of fir chips
[0137] The flattened fir wood chips were soaked in a mixed aqueous solution of formic acid-hydrochloric acid-ethanol (molar ratio of 0.05:1:0.1) with a total concentration of 1.5 mol / L at room temperature for 10 hours to thoroughly clean the extracts and inorganic salts in the fir wood pipes.
[0138] Subsequently, the fir wood chips were soaked in deionized water at room temperature for 2 h and washed repeatedly until the pH value was close to 7.0.
[0139] Rinse once more with 95% ethanol to ensure thorough cleaning.
[0140] The cleaned fir chips were placed in a vacuum oven at 50° C. and dried for 24 hours to obtain fir chips with transparent pores.
[0141] Step 3: Carbonization of fir chips
[0142] The fir wood chips with transparent pores were placed in a tubular furnace, and slowly heated to 800°C at a heating rate of 5°C / min under nitrogen protection, and kept warm for 2 hours to fully carbonize the fir wood chips.
[0143] After carbonization, the temperature was lowered to 500 °C at a rate of 5 °C / min and then naturally cooled to room temperature.
[0144] Take out the fir carbon sheet, use 220-grit sandpaper to smooth the collapsed or raised parts of the surface, and finally polish it into a rectangular block with a size of 1 cm×2 cm×0.1 cm.
[0145] After being rinsed alternately with deionized water and 95% ethanol, the carbon sheets were dried in a vacuum oven at 60° C. for 12 hours to obtain fir carbon sheets with uniform specifications, certain conductivity, smooth surface and transparent pores.
[0146] Step 4: Treatment of nickel foam and molten salt electrolysis of fir wood carbon sheets
[0147] Clean nickel foam (1 mm thick, purity 99.9%, porosity 98%, pore size 0.3 mm) was taken and immersed in a mixed solution of cobalt acetate and nickel acetate (molar ratio 3.0) in ethanol with a total concentration of 10 mmol / L for 10 minutes.
[0148] Take out the nickel foam, spread it flat in a glass container, and let it dry naturally at room temperature.
[0149] A rectangular fir carbon sheet with transparent pores was wrapped with dried nickel foam and subjected to a load of 15 kN / m 2 The nickel foam was squeezed under a certain pressure to ensure that it was in full contact with all surfaces of the fir wood carbon sheet.
[0150] The nickel foam-wrapped fir wood carbon sheet was fixed on a stainless steel conductive support using 304 stainless steel wire as the working electrode.
[0151] This working electrode, together with a nickel-chromium alloy rod fixed on a stainless steel conductive support (as a counter electrode and a reference electrode), was placed in a 950°C molten salt electrolyte (Na2CO3 / K2CO3 molar ratio of 59:41) under an argon atmosphere for electrolysis.
[0152] A voltage of -2.1 V was applied to the working electrode, and electrolysis was performed for 12 hours.
[0153] After the electrolysis was completed, the sample was cooled to room temperature, taken out from the nickel foam, and immersed in 1 M hydrochloric acid to remove the residual carbonate.
[0154] The sample was rinsed with deionized water until the pH reached neutral and dried under vacuum at 60 °C for 12 h to obtain the self-supporting carbon material.
[0155] (II) Application performance test of self-supporting carbon electrodes
[0156] This time, its application in zinc ion supercapacitors was tested. The self-supporting carbon electrode was used as the working electrode, and the zinc foil electrode was used as the counter electrode and reference electrode. Through the two-electrode system, the prepared electrode was subjected to constant current charge and discharge tests (charge and discharge voltage range 0.2-1.8V) in 2M ZnSO4 electrolyte at room temperature using a battery charge and discharge equipment (CT2001A, Wuhan Blue Electric Electronics Co., Ltd.).
[0157] According to the formula C = I × △t / M, the specific capacity C of the prepared sample at different charge and discharge current densities can be calculated based on the charge and discharge curve. Where △t (h) represents the discharge time, I (mA) represents the discharge current, and M (g) represents the mass of the entire self-supporting electrode material.
[0158] The results show that at 2.0 mA / cm 2 Under the current density, the mass specific capacity of the prepared self-supporting carbon electrode can reach 63 mAh / g, indicating that the self-supporting carbon electrode prepared by the method of the present invention has excellent electrochemical properties and is a potential candidate for zinc ion supercapacitor electrode.
[0159] Comparative Example
[0160] The total concentration of the ethanol mixed solution of cobalt acetate and nickel acetate (molar ratio of 1.0) in step 4 of Example 1 was adjusted from 5mmol / L to 0mmol / L, and a similar process was used to prepare a self-supporting carbon material. The application performance test method of Example 1 was used to test the application of the prepared carbon material in zinc ion supercapacitors. The results showed that at 2.0mA / cm 2 Under the current density, the mass specific capacity of the prepared self-supporting carbon electrode is only 45 mAh / g, which is significantly lower than the specific capacity of 67 mAh / g of the self-supporting carbon electrode prepared by using a mixed solution of cobalt acetate and nickel acetate (molar ratio of 1.0) in ethanol with a total concentration of 5 mmol / L. This shows that the invention ingeniously uses nickel foam with cobalt acetate and nickel acetate pre-adsorbed on the surface to wrap and encapsulate the wood and bamboo carbon sheet for molten salt electrolysis, which helps to improve the electrochemical performance of the prepared self-supporting carbon electrode.
[0161] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A method for preparing a self-supporting carbon electrode based on wood and bamboo materials, characterized in that: Includes steps: (1) fully carbonizing a wood-bamboo sheet having transparent pores in an inert atmosphere to obtain a wood-bamboo carbon sheet; (2) The nickel foam is immersed in a solution containing cobalt acetate and nickel acetate, then taken out and dried, wrapped with wood and bamboo carbon sheets, and subjected to a load of 5 to 15 kN / m 2 The nickel foam is squeezed under the pressure to make it fully contact with all surfaces of the wood and bamboo carbon sheet; (3) The wood and bamboo carbon sheet wrapped with nickel foam obtained in step (2) is fixed on a first conductive support as a working electrode, and placed together with a counter electrode and a reference electrode in a molten salt electrolyte under an inert atmosphere for electrolysis, a voltage of -2.1 to -2.3 V is applied to the working electrode, and the electrolysis is performed for 8 to 12 hours to achieve pore formation and graphitization. After the electrolysis is completed, the wood and bamboo carbon sheet sample is taken out from the nickel foam, washed, and dried to obtain a self-supporting carbon electrode.
2. The preparation method according to claim 1, characterized in that: In step (1), the method for preparing the wood-bamboo slices having transparent pores comprises: The peeled bamboo is cut into bamboo slices, polished and then soaked in a mixed aqueous solution of formic acid-hydrochloric acid-ethanol to thoroughly clean the extract and inorganic salt in the bamboo pipes, then taken out, washed and dried to obtain the bamboo slices with transparent pores.
3. The preparation method according to claim 2, characterized in that: In the method for preparing the wood-bamboo sheet with transparent pores: The size of the cut wood and bamboo pieces is: 2 cm wide, 3 cm long, and 0.3 cm thick; Use 400 grit sandpaper at 30 kN / m 2 The grinding is performed under a pressure of The mixed aqueous solution of formic acid-hydrochloric acid-ethanol is obtained by mixing a formic acid aqueous solution, a hydrochloric acid aqueous solution and ethanol; In the mixed aqueous solution of formic acid-hydrochloric acid-ethanol, the total concentration of formic acid, hydrochloric acid and ethanol is 0.8-1.5 mol / L, the molar ratio of formic acid to hydrochloric acid is 0.05-0.2:1, and the molar ratio of ethanol to hydrochloric acid is 0.08-0.12:1; Wash with deionized water and ethanol until the pH of the wood and bamboo chips is 7; The drying is performed by vacuum drying at a drying temperature of 50°C.
4. The preparation method according to claim 1, characterized in that: In step (1): The wood and bamboo chips include one or more of pine chips, bamboo chips, and fir chips; The inert atmosphere is a nitrogen atmosphere; The carbonization temperature is 800-1000°C, the heating rate is 3-5°C / min, and the carbonization time is 1-2 hours; After carbonization, the temperature was lowered to 500°C at a rate of 3-5°C / min, and then naturally cooled to room temperature; The carbonized product is polished, cleaned and dried to obtain a wood-bamboo carbon sheet; Use 220-grit sandpaper to grind to obtain a cuboid with a width of 1 cm, a length of 2 cm, and a thickness of 0.1 cm; Wash with deionized water and ethanol; The drying is performed by vacuum drying at a drying temperature of 60°C.
5. The preparation method according to claim 1, characterized in that: In step (2): The thickness of the nickel foam is 1-2 mm, the porosity is 95%-98%, and the pore size is 0.2-0.5 mm; In the solution containing cobalt acetate and nickel acetate, the total concentration of cobalt acetate and nickel acetate is 5-10 mmol / L, and the molar ratio of cobalt acetate to nickel acetate is 1-3:1; The solvent in the solution containing cobalt acetate and nickel acetate is ethanol; The foamed nickel is immersed in the solution containing cobalt acetate and nickel acetate for 5 to 15 minutes.
6. The preparation method according to claim 1, characterized in that: In step (3): The wood-bamboo carbon sheet wrapped with nickel foam is fixed on a first conductive support using 304 stainless steel wire as a working electrode; The first conductive bracket is a stainless steel conductive bracket; A nickel-chromium alloy rod fixed on a second conductive support is used as a counter electrode and a reference electrode; The second conductive bracket is a stainless steel conductive bracket; The inert atmosphere is an argon atmosphere; The temperature of the molten salt electrolyte is 850-950°C; The molten salt electrolyte is a mixed molten salt of sodium carbonate and potassium carbonate; In the molten salt electrolyte, the molar proportion of sodium carbonate is 55% to 65%, based on the total molar number of sodium carbonate and potassium carbonate being 100%; The washing is performed sequentially using hydrochloric acid and deionized water, wherein the hydrochloric acid is used to wash away the residual salt, and the deionized water is used to wash the wood and bamboo carbon sheet sample until the pH reaches neutral; The drying is performed by vacuum drying at a drying temperature of 60°C.
7. A self-supporting carbon electrode prepared according to the preparation method according to any one of claims 1 to 6.
8. Use of the self-supporting carbon electrode according to claim 7 in preparing a supercapacitor electrode.
9. The use according to claim 8, characterized in that: The supercapacitor is a zinc ion supercapacitor or a lithium ion supercapacitor.
Citation Information
Patent Citations
Electrochemical method for converting amorphous carbon into graphite
CN103510103A
Electrochemical preparation method for silicon / carbon composite material by using molten salt
CN108011084A
Preparation method of graphitized carbon powder
CN112301364A
Method for converting amorphous carbon to graphitized carbon nanofibers
CN112442761A
Hybrid zinc battery electrode, preparation method thereof and application of hybrid zinc battery electrode in preparation of battery
CN117855372A
Cited By
Reference electrode
CN119959322A